Russian literature in the context of philosophical-methodological principles G. V. Plekhanov - Kulak, Nikita I. (Journal of the Belarusian State University. Philosophy and Psychology, 2020)
The worldview of representatives of Russian literature of the XIX century is investigated (N. G. Chernyshevsky, V. G. Belinsky, L. N. Tolstoy) in the context of philosophical and methodological principles G. V. Plekhanov: a marxist understanding of the dialectical course of social phenomena, a materialistic explanation of history, the relationship of the abstract and the concrete, the anthropological essence of man. In accordance with these principles, their intellectual views are evaluated, thereby revealing the historical and philosophical concept of G. V. Plekhanov. It is shown that the appeal to philosophical and methodological principles allows us to identify the deep relationship of the historical and philosophical concept of G. V. Plekhanov with Russian tradition, which is most clearly reflected in the analysis of N. G. Chernyshevsky, V. G. Belinsky, L. N. Tolstoy. The principle of materialistic monism in comprehending the worldview of Russian writers became central to his concept, which led to the philosophical simplification of the artistic creations of Russian and foreign thought. This principle turned out to be general in the methodology of G. V. Plekhanov, including in the ideological assessment of Russian literature and in its historical and philosophical concept, which remains not fully understood in Russian philosophical thought.
Keywords: philosophical methodology G. V. Plekhanov; Russian literary critical though; N. G. Chernyshevsky; V. G. Belinsky; L. N. Tolstoy